Answer:
The person above me has the correct answer and solves it in the correct way.
Explanation:
This is what I used as my answer though.
Distance Formula: d = √(x2-x1)^2 + (y2-y1)^2
BC = √(x2-x1)^2 + (y2-y1)^2
B = (6,2)
C = (2,-1)
BC = √(2-6)^2 + (-1-2)^2
BC = √(-4)^2 + (-3)^2
BC = √16+9
BC = √25
BC = 5
Answer/Step-by-step explanation:
1.
✔️Coordinates of vertices ABC:
A(2, 2)
B(6, 2)
C(2, -1)
✔️AC = |2 - (-1)| = 3 units
AB = |2 - 6| = 4 units
2. Distance formula =>
Distance between B(6, 2) and C(2, -1):
Where,
5.1m questions
6.7m answers